Training of Future Primary School Teachers for the Use of Audio-Visual Teaching Aids - Ihor Kuzio (Pedagogical Discourse, 2011)
On the basis of the analysis of psychological and educational literature the main issues of training of future primary school teachers to the use of audio-visual means of training in their work are elucidated in the article, the key issues that arise in the process of teaching students are examined.